RETRACTED: Longitude Variation of the microRNA-497/FGF-23 Axis during Treatment and Its Linkage with Neoadjuvant/Adjuvant Trastuzumab-Induced Cardiotoxicity in HER2-Positive Breast Cancer Patients - Liu, Hui; Hu, Xiaoyan; Wang, Lingyun; Du, Tao; Feng, Jing; Li, Ming; Liu, Lei; Liu, Xiaofang (Frontiers in Surgery, 2022)
Purpose: MicroRNA-497 (miR-497) is previously reported to target fibroblast growth factor 23 (FGF-23) and regulates cardiac injury, while their value in predicting drug-induced cardiotoxicity is not reported. Thus, the current study aimed to investigate the correlation of miR-497/FGF-23 with neoadjuvant/adjuvant trastuzumab induced cardiotoxicity in human epidermal growth factor receptor 2 (HER2)-positive breast cancer patients. Methods: 97 HER2-positive surgical breast cancer patients received neoadjuvant/adjuvant trastuzumab contained regimens were enrolled, then their peripheral blood mononuclear cells (PBMC) and serum were collected at baseline, after neoadjuvant treatment, at 3 months (M3), 6 months (M6), 9 months (M9), 12 months (M12) after surgery. The PBMC was used for miR-497 measurement and the serum was used for FGF-23 measurement. The cardiotoxicity events and incidence were recorded. Results: A total of 24 (24.7%) patients occurred cardiotoxicity during the treatment period. MiR-497 decreased from baseline (median: 0.955) to M12 after surgery (median: 0.602) (P<0.001), while FGF-23 increased from baseline (median: 0.390 ng/mL) to M12 after surgery (median: 0.566 ng/mL) (P<0.001); besides, miR-497/FGF-23 axis greatly reduced from baseline (median: 2.545) to M12 after surgery (median: 1.222) (P<0.001). At most time points, miR-497 negatively related to FGF-23 (all P<0.05). Notably, miR-497/FGF-23 axis at all time points (including baseline, post-neoadjuvant treatment, M3, M6, M9 and M12) related to lower risk of cardiotoxicity (all P<0.05). Furthermore, miR-497/FGF-23 axis also positively correlated with left ventricular ejection fraction (LVEF) at all time points (all P<0.01). Conclusion: MiR-497/FGF-23 axis serves as a potential indicator predicting trastuzumab-induced cardiotoxicity in HER2-positive breast cancer patients.